DEAR4, a Member of DREB/CBF Family, Positively Regulates Leaf Senescence and Response to Multiple Stressors in Arabidopsis thaliana - Zhang, Zenglin; Li, Wei; Gao, Xiaoming; Xu, Mengmeng; Guo, Yongfeng (Frontiers in Plant Science, 2020)
Leaf senescence is a programmed developmental process regulated by various endogenous and exogenous factors. Here we report the characterization of the senescence-regulating role of DEAR4 (AT4G36900) from the DREB1/CBF (dehydration-responsive element binding protein 1/C-repeat binding factor) family in Arabidopsis. The expression of DEAR4 is associated with leaf senescence and can be induced by ABA, JA, darkness, drought and salt stress. Transgenic plants over-expressing DEAR4 showed a dramatically enhanced leaf senescence phenotype under normal and dark conditions while the dear4 knock-down mutant displayed delayed senescence. Furthermore, DEAR4 over-expressing plants showed decreased seed germination rate under ABA and salt stress conditions as well decreased drought tolerance, indicating thatDEAR4 was involved in both senescence and stress response processes. Furthermore, we found that DEAR4 protein displayed transcriptional repressor activities in yeast cells. DEAR4could directly repress the expression of a subset of COLD-REGULATED (COR) and RESPONSIVE TO DEHYDRATION (RD) genes which have been shown to be involved in leaf longevity and stress response. Also we found that DERA4 could induce the production of ROS (Reactive oxygen species), the common signal of senescence and stress responses, which give us the clue that DEAR4may play an integrative role in senescence and stress response via regulating ROS production.